Pengaruh Independensi, Kompetensi, Profesionalisme, dan Integritas Terhadap Kualitas Audit dengan Etika Auditor Sebagai Moderasi - Naila Syamlan; Sistya Rachmawati (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2021)
The objective of this research is to examine and to analyze the effect of Independence (I), Competence (K), Professionalisme (P), and Integrity (IT) towards The Quality of Audit with Auditor Ethics as Moderating Variable in the public accounting firm second thier located in DKI Jakarta. The sample was extracted using random sampling method. The research sample of 120 respondents in 6 have the public accounting firm second tier located in Jakarta. This research uses multiple regression analysis method. In this study has six variables, which consists of independent moderating and dependent variables. The independent variable: independence, competence, professionalism and integrity, while the dependent variable is the quality of its audit. The moderating variable is auditor ethics. Based on the results of this study concluded that the independence, competence, profesionalism, and integrity positive significant effect on audit quality.